2020
DOI: 10.1155/2020/2868564
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloidiasis in Africa: Systematic Review and Meta-Analysis on Prevalence, Diagnostic Methods, and Study Settings

Abstract: Background. Strongyloidiasis is an intestinal parasitic infection mainly caused by Strongyloides stercoralis. Although it is a predominant parasite in tropics and subtropics where sanitation and hygiene are poorly practiced, the true prevalence of strongyloidiasis is not known due to low-sensitivity diagnostic methods. Objective. This systematic review and meta-analysis is aimed at determining the pooled prevalence of strongyloidiasis in African countries, stratified by diagnostic methods, study settings, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 92 publications
(34 reference statements)
0
8
2
Order By: Relevance
“…Another study revealed that larva output in faecal specimens ranged from 0.003 larvae per gram to 151.2 larvae per gram ( Khieu et al, 2013 ). However, the use of a Kato-Katz technique only in this study is a limitation and cannot efficiently detect all S. stercoralis infection ( Machicado et al, 2012 ; Hailu et al, 2020 ; WHO, 2020 ). Thus, the result of our study should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Another study revealed that larva output in faecal specimens ranged from 0.003 larvae per gram to 151.2 larvae per gram ( Khieu et al, 2013 ). However, the use of a Kato-Katz technique only in this study is a limitation and cannot efficiently detect all S. stercoralis infection ( Machicado et al, 2012 ; Hailu et al, 2020 ; WHO, 2020 ). Thus, the result of our study should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, a prevalence of 24.4% among schoolchildren in Cambodia was obtained using combined two methods, Baermann and Koga agar plate culture techniques ( Khieu et al, 2013 ). Additionally, a recent systematic review of 82 studies in Africa found Kato-Katz to be a less popular tool for diagnosis of S. stercoralis with just 2 of these studies utilising the technique for detection of S. stercoralis ( Hailu et al, 2020 ). The study also found that Kato-Katz detected S. stercoralis larvae in only 8 out of 810 participants ( Hailu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the global prevalence of S. stercoralis reported different results [51,52] and it was recently estimated at 8.1% of the population, corresponding to 613.9 million people [53]. It is widely distributed around the globe with higher prevalence in tropical and subtropical regions, particularly Latin America [54], South East Asia, Sub-Saharan Africa [55], southern United States and the Appalachian region [56]. Risk is higher in rural populations with poor sanitation and low socio-economic status [57] as well as in migrants and refugees from endemic areas [58][59][60] Travelers staying for prolonged periods in endemic regions are also at risk [61].…”
Section: Epidemiologymentioning
confidence: 99%